Reframing the Case Method in Entrepreneurship Education (Edward Elgar Publishing, 2022)
Open access This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. This book explores how entrepreneurship can be taught through case studies, arguing that entrepreneurship education needs specific cases and case methods to teach students entrepreneurial skills and mindsets. Providing unique perspectives and examples on how case teaching can be applied in entrepreneurship education, the book draws together a wide range of real-life case studies.